Cardiac ischaemia and rhythm disturbances during elective colonoscopy. Issue 3 (23rd September 2010) - George, A T; Davis, C; Rangaraj, A; Edwards, C; Chamary, V L; Khan, H; Javed, M; Campbell, P G; Allison, M C; Swarnkar, K J
Abstract : Background: The number of colonoscopic procedures continues to rise rapidly. With widespread adoption of colonoscopy based bowel screening programmes, this rising trend is set to continue. Aims: This study aimed to identify whether elective colonoscopy could provoke cardiac rhythm disturbances and/or myocardial ischaemia, as evidenced by 12 lead Holter ECG recordings and troponin I (cTnI) changes. Materials and methods: Patients were stratified into three groups based on the presence of cardiac disease or cardiovascular risk factors. They underwent real time 12 lead Holter monitoring before, during and after colonoscopy. Bloods were taken for pre- and post-procedure cTnI estimation. Results: Holter ECG recordings of the three groups showed a high incidence of new but silent ischaemic and arrhythmic ECG changes during the colonoscopy in patients with documented but stable heart disease and to a lesser extent in those patients with one or more risk factors for heart disease. Three patients had high cTnI concentrations both before and after colonoscopy. Two patients with known heart disease died within 30 days of colonoscopy. Conclusions: This study demonstrates for the first time the occurrence of potentially clinically significant ST-T wave changes and rhythm disturbances during elective colonoscopy in patients with known heart disease and to a lesser extent in those patients with a known cardiovascular risk profile.